THE BASICS OF TEACHING ENGLISH USING INFORMATION TECHNOLOGY - Angelina Kim (ZAMONAVIY TA’LIMDA FAN VA INNOVATSION TADQIQOTLAR, 2025)
Information technology, interactive learning, collaborative learning, personalized learning, gamification, digital literacy, educational technology, teaching tools, digital resources, remote learning, educational innovation. ABSTRACT This article explores the integration of information technology (IT) in teaching English, highlighting its role in enhancing the language learning process. It discusses various IT tools and resources, such as online platforms, multimedia content, and collaborative learning tools, that enable teachers to create interactive, engaging, and personalized lessons. The article emphasizes how IT can improve vocabulary acquisition, listening comprehension, and speaking skills, as well as foster collaboration among students. Additionally, the article addresses the challenges of ensuring equal access to technology and balancing digital tools with traditional teaching methods. Ultimately, it provides an overview of how information technology can be effectively utilized to enrich the English language learning experience.